Sertão-fronteira: a travessia dos homens provisórios - Amanda Alves Maciel Rocha (2019)
This research tries to understand the processes of construction of alterities and forms of resistance of the sertanejos - subordinated to a colonial regime of subalternity - from the historical and political conditions in which they are inserted. For this, we propose an epistemological and enunciative turn driven, mainly, by the voices of the local subjects. Modernity is in crisis and, from this fissure, the possibility arises to return to other epistemologies - other rationality matrices - that still resist the invisibility condition to which they are submitted. Together with the residents of Paredão de Minas - a district of the municipality of Buritizeiro / MG - we reflect on issues that surpass the local order and raise a wide debate about the coloniality of knowledge and power, cultural differences that combine at borders, forms of resistance and oppression, of the agricultural frontier that advances over the Cerrado of Minas Gerais, of the sertões that escape us, and of the roads to be built toward social emancipations.